Optimization of Income Tax Revenue in Land and Building Rights Transfer Transactions - Robbani, Anila; Raffy Arnanda Faturrohman; Ahmad Hananul Amin (Jurnal Justice Dialectical, 2024)
Income tax has the potential for revenue from transactions involving the transfer of land and building rights. However, there are still challenges to its optimal implementation. The purpose of this research is, first, to understand the mechanism of income tax imposition on transactions involving the transfer of land and buildings and, secondly the challenges in optimizing income tax on transactions involving the transfer of land and buildings. This research employs the normative legal research method, which incorporates a legislative and conceptual perspective. The legal system theory examines the factors that challenge the optimization of income tax on the transfer of land and building rights. The research results show, first, the mechanism of PPh on PHTB is imposed on the amount of income received or obtained by the party transferring or selling the rights to land and/or buildings. The payment of PPh occurs prior to the signing of the land transfer deed. Secondly, the optimization challenge often arises from taxpayers collaborating to evade the obligation to pay income tax on the transfer of land and buildings. Three factors contribute to non-compliance: the evolving legal framework and intricate mechanisms, the existence of land law enforcers within the legal structure who aid taxpayers in evading income tax payments, and the prevailing legal culture that lacks awareness of the procedures and significance of paying income tax on land and building transfers. Therefore, the tax sector needs to implement a series of tax policy strategies to meet national revenue targets.